Integration of ATAC-seq and RNA-seq analysis identifies key genes affecting intramuscular fat content in pigs - Xu, Zhong; Wu, Junjing; Zhou, Jiawei; Zhang, Yu; Qiao, Mu; Sun, Hua; Li, Zipeng; Li, Lianghua; Chen, Nanqi; Oyelami, Favour Oluwapelumi; Peng, Xianwen; Mei, Shuqi (Frontiers in Nutrition, 2022)
Meat quality is one of the most important economic traits in pig breeding and production, and intramuscular fat (IMF) content is the major factor in improving meat quality. The IMF deposition in pigs is influenced by transcriptional regulation, which is dependent on chromatin accessibility. However, how chromatin accessibility plays a regulatory role in IMF deposition in pigs has not been reported. In this study, we used the assay for transposase-accessible chromatin using sequencing (ATAC-seq) and RNA sequencing (RNA-seq) analysis to identify the accessible chromatin regions and key genes affecting IMF content in one pig breed with extremely high and low IMF content. First, we identified 21960 differential accessible chromatin peaks and 297 differentially expressed genes. The motif analysis of differential peaks revealed several potential cis-regulatory elements containing binding sites for transcription factors with potential roles in fat deposition, including Mef2c, CEBP, Fra1, and AP-1. Then, by integrating the ATAC-seq and RNA-seq analysis results, we found 47 genes in IMF_H and IMF_L groups. For these genes, we observed a significant positive correlation between the differential gene expression and differential ATAC-seq signal (r2 = 0.42). This suggests a causative relationship between chromatin remodeling and the resulting gene expression. We identified several candidate genes (PVALB, THRSP, HOXA9, EEPD1, HOXA10, and PDE4B) that might be associated with fat deposition. Through the PPI analysis, we found that PVALB gene was the top hub gene. In addition, some pathways that might regulate fat cell differentiation and lipid metabolism, such as the PI3K-Akt signaling pathway, MAPK signaling pathway, and calcium signaling pathway, were significantly enriched in the ATAC-seq and RNA-seq analysis. To the best of our knowledge, our study is the first to use ATAC-seq and RNA-seq to examine the mechanism of IMF deposition from a new perspective. Our results provide valuable information for understanding the regulation mechanism of IMF deposition and an important foundation for improving the quality of pork.